A Self-Regulated English Medical Terminology E-Module: Design and Validation for Health Sciences Students - Farida Noor Rohmah; Yuyun Nailufar; Royan Utsani (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
English for Medical Purposes (EMP) is essential for equipping health science students to communicate proficiently in both academic and clinical environments. Nonetheless, current English for Specific Purposes (ESP) programs frequently prioritize general proficiency over the systematic instruction of discipline-specific vocabulary via digital platforms. This study aimed to create and validate a self-directed e-module intended to improve medical English terminology acquisition among health science students. The study employed a Research and Development (R&D) methodology based on the ADDIE model, encompassing the design, development, implementation, and assessment phases. The Canva-based e-module integrated multimedia components, including pronunciation audio, interactive exercises, and self-assessment activities. Expert validation yielded an average feasibility score of 91.25% for material aspect and 93.75% for media aspect, while student practicality reached 89.02%, indicating strong pedagogical and technological soundness. The results confirm that systematic instructional design combined with interactive digital tools effectively supports autonomous vocabulary learning in ESP contexts. This study contributes a replicable framework for localized digital material development in medical English education, advancing learner autonomy and engagement in health science programs.